A survey Study to Measure the level of Motivation a Squash lesson for junior students in the College of Physical Education and Sports Sciences - Sami , Marwan; Dakheel, Hasanain; Crook, Tamara (Journal of Physical Education, 2025)
Human behavior is one of the topics that has captured the attention of researchers throughout the ages, and motivation is one of the manifestations of this behavior, which indicates the extent of interest in a particular topic and their unwillingness to rush towards a particular topic. The topic of motivation is one of the important topics of interest to the teacher and coach in the field of sports. The aim of this research was identifying the level of motivation for junior students, and the differences in the dimensions of motivation for junior students in squash lessons. We used the descriptive survey method, and the research sample was chosen randomly. Only male of the junior students in the College of Physical Education and Sports Sciences at the University of Baghdad, where the research sample represents 15 % of the research community. We used the scale distributed in the form for measuring the motivation, and the results showed there are differences in the level of motivation among junior students in motivation scale, and there are not significant between the five dimensions for motivation scale. And recommend to Focus on the psychological aspects of squash students and develop their self-confidence to enable them to control their emotions. Finally, we must engage the junior students in training and refereeing courses, in cooperation with the Federation.